Pembelajaran Berdiferensiasi pada Mata Pelajaran PAI: Tinjauan Literatur Berbasis Dimensi School Well‑Being - Cahyono, Acep; Wahyuni, Ana Dwi; Umam, Mustolikh Khabibul (Universitas Cokroaminoto Yogyakarta, 2025)
This literature review article discusses differentiated learning in Islamic Religious Education (PAI) based on four dimensions of school well-being: having, loving, being, and health. The study aims to summarize empirical and conceptual findings regarding differentiation strategies that support students' holistic well-being. The method includes a systematic search of literature on Google Scholar (2016–2025, Sinta 1–6) using the keywords